Improved Performance of Mean Greedy Algorithm for Chunk Allocation in SC-FDMA Uplink Systems using Joint-User and Chunk-Based Allocation - Arfianto Fahmi; Muhamad Asvial; Dadang Gunawan (Journal of ICT Research and Applications, 2013)
In this paper, the problem of subcarrier allocation on chunk-by-chunk basis in SC-FDMA uplink systems is investigated. Improved mean enhanced greedy algorithms are proposed for performing joint-user and chunk-based allocation at each transmission time interval. Selection criteria based on spectral efficiency and fairness are also proposed to choose the final allocation at each transmission time interval. Simulation results show that when the number of users and the velocity of the users were varied, the improved algorithms that use selection criteria based on spectral efficiency and fairness could outperform the existing mean greedy algorithms that employ user-based allocation in terms of spectral efficiency and fairness. Moreover, the improved algorithms not only showed better performance but also had the same time complexity as the existing mean greedy algorithms.